2009
DOI: 10.1007/s00251-009-0408-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of killer cell immunoglobulin-like receptors (KIR) and their HLA-C ligands in two Iranian populations

Abstract: Killer cell immunoglobulin-like receptors (KIR) gene frequencies vary between populations and contribute to functional variation in immune responses to viruses, autoimmunity and reproductive success. This study describes the frequency distribution of 12 variable KIR genes and their HLA-C ligands in two Iranian populations who have lived for many generations in different environments: the Azerbaijanis at high altitude and the Jonobi people at sea level. The results are compared with those published for other hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 37 publications
2
20
1
Order By: Relevance
“…Defaults in trophoblast invasion and/or vascular remodelling are hallmarks of pathological pregnancy, such as pre‐eclampsia. Genetic studies suggested that special combinations of fetal HLA‐C haplotypes and maternal dNK cell inhibitory KIRs increased the likelihood of pre‐eclampsia . In a similar manner, the association of some HLA‐C genotypes and maternal KIRs has been linked to defaults in trophoblast invasion.…”
Section: Functions Of Dnk Cells Under Normal Pregnancy: Mother's Littmentioning
confidence: 98%
“…Defaults in trophoblast invasion and/or vascular remodelling are hallmarks of pathological pregnancy, such as pre‐eclampsia. Genetic studies suggested that special combinations of fetal HLA‐C haplotypes and maternal dNK cell inhibitory KIRs increased the likelihood of pre‐eclampsia . In a similar manner, the association of some HLA‐C genotypes and maternal KIRs has been linked to defaults in trophoblast invasion.…”
Section: Functions Of Dnk Cells Under Normal Pregnancy: Mother's Littmentioning
confidence: 98%
“…A protective association of some activating KIRs of the telomeric B haplotype region, particularly 2DS1 as well as 3DS1, 2DS5, and 2DL5, with RSA was reported in an English Caucasian population composed of 95 RSA cases and 269 controls (Moffett and Colucci, 2015). Moreover, in the same study population, the AA haplotype was found to be positively associated with recurrent miscarriage (Hiby et al, 2010b;Moffett and Colucci, 2015). reported a protective effect of the KIR AA haplotype and inhibitory genes in an Asian Indian population composed of 205 women with a history of RSA and 224 controls belonging to different ethnic groups.…”
Section: Discussionmentioning
confidence: 68%
“…In this study, authors did not consider the 2DL5 gene and failed to amplify the 2DS3 genes in both case and groups (Ay et al, 2019). These conflicting results are a subject of controversy and debate regarding the method of typing and the matching of patients and controls according to ethnic origin as well as exclusion criteria/inclusion in the choice of patients and controls (Faridi and Agrawal, 2009;Hiby et al, 2010b). Indeed, in almost all studies, the patients and controls were not selected according to the same criteria regarding the number of spontaneous abortions in the patient group and the number of pregnancies in the control group.…”
Section: Discussionmentioning
confidence: 81%
“…52 We found that the gene carrier frequencies were very similar to those of published KIR gene carrier frequencies from an English cohort of Caucasoid ethnicity. 54 (Figure 1a). The software was unable to predict possible haplotype pairs for 3% (n=25) of cases.…”
Section: High Accuracy For Identifying Kir Gene Absence/presencementioning
confidence: 99%